All we need is love? Trade-adjustment, inequality, and the role of the partner - Katrin Huber; Erwin Winkler (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We examine the distributional effect of Germany's trade integration with China and Eastern Europe and show that there are considerable differences between the household level and the individual level impact. The trade shock increased inequality of individual earnings. At the household level, however, about 40% of this distributional effect is reduced by a simple insurance effect that occurs if partners within married and unmarried couples are differently affected by the trade shock. The insurance effect is substantial since the trade shock had a large variation across industries and 80% of individuals within couples are employed in different industries. Our analysis also reveals that many workers who individually benefit from the trade shock turn into 'losers' at the household level because they have a partner who experiences a strong negative impact. All in all, this paper suggests that a household level perspective is essential in order to understand the exact distributional consequences of globalization.
Keywords: J31; F16; 330; Earnings Inequality; International Trade; Household; Insurance